Reforming the mathematical method in the Iraqi parliament election system - Ali Hady Hamidy AL-Shkrawy (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Electoral Reform Is An Integral Part Of The Overall Reform In Iraq, Which Should Include The Legal Framework For The Election And The Calculation Method, Strengthening The Electoral Administration, And Evaluation Of The Voters And Candidates Behavior. This Research Is Assumed The Following Assumptions: 1-The Majority Of Researchers Did Not Distinguish Between Whole Electoral System And The Method Of Calculation On The Distribution Of Parliamentary Seats. 2-That The Application Of The Calculation Method Represents A Later Stage On The Ballot Stage Of The Election Process, That Is Part Of It. 3-The Calculation Method Specializes In The Extraction Of The Ballot Results, Winners And Losers, Allocated To Constituencies Parliamentary Seats Or Executive To Positions In The Elections Or Referendum. 4-The Calculation Method Applied In Iraq Will Not Lead To A Just Results , To Be An Expression Of Real Public Opinion Tendencies Resulted In The Misapplication Of The Original And Amended Sainte Laguë Method In Iraq, A Set Of Problems Was The Lack Of Use In The Distribution Of Parliamentary Seats Women Quota And The Components Quota On The One Hand, And When Used The Method In The Distribution Of Public Parliamentary Seats Led To A Distortion Of The Will Of The Real Voters, And Distort The Principles Of Political And Partisan Pluralism In Some Of Its Findings On The Other Hand, Which That Confirmed The Presence Of A Defect In A General Electoral System And The Calculation Method On Both Theoretical And Practical In Iraq . Among The Most Important Proposals That Could Be Presented Are: That The House Of Representatives Held A National Conference Of Iraqi University Professors, Especially For Professors Of Law, Political Science, Media, Information Technology, And Mathematics, In Order To Reach An Integrated Design An Electoral System In Line With The Reality Of Iraq And The Conditions Of The Transition, To Achieve Equitable Distribution Of Parliamentary Seats On Competing Lists Of Winning The Constituencies At The National And Local Levels.